Spatial Distribution of Carbon Stored in Forests of the Democratic Republic of Congo. Issue 1 (December 2017) - Xu, Liang; Saatchi, Sassan; Shapiro, Aurélie; Meyer, Victoria; Ferraz, Antonio; Yang, Yan; Bastin, Jean-Francois; Banks, Norman; Boeckx, Pascal; Verbeeck, Hans; Lewis, Simon; Muanza, Elvis; et al.
Abstract National forest inventories in tropical regions are sparse and have large uncertainty in capturing the physiographical variations of forest carbon across landscapes. Here, we produce for the first time the spatial patterns of carbon stored in forests of Democratic Republic of Congo (DRC) by using airborne LiDAR inventory of more than 432, 000 ha of forests based on a designed probability sampling methodology. The LiDAR mean top canopy height measurements were trained to develop an unbiased carbon estimator by using 92 1-ha ground plots distributed across key forest types in DRC. LiDAR samples provided estimates of mean and uncertainty of aboveground carbon density at provincial scales and were combined with optical and radar satellite imagery in a machine learning algorithm to map forest height and carbon density over the entire country. By using the forest definition of DRC, we found a total of 23.3 ± 1.6 GtC carbon with a mean carbon density of 140 ± 9 MgC ha−1 in the aboveground and belowground live trees. The probability based LiDAR samples capture variations of structure and carbon across edaphic and climate conditions, and provide an alternative approach to national ground inventory for efficient and precise assessment of forest carbon resources for emission reduction (ER) programs.